A Visual Evaluation of a Classification Method for Investigating the Physicochemical Properties of Portuguese Wine - J. Beh, Eric; I. Holdsworth, Clovia (Current Analytical Chemistry, 2012)
In a recent study of about 6500 white and red Portuguese wines, a formal method of classification was considered based on 11 key chemical and physical properties. These properties were all deemed as being important for influencing the quality of wine that is produced in the area. In this paper, we explore these physiochemical characteristics and begin by providing a glimpse into understanding the link between these characteristics and wine quality. A more formal analytical approach is considered that involves undertaking a multiple-regression analysis of these characteristics. A key aspect of this paper is to provide a graphical comparison of this formal method of classification with the classification given to the wines by three experienced assessors. The graphical approach considered in this paper is correspondence analysis applied to the confusion matrices formed by cross-classifying the wine levels given by the assessors and those specified by more formal classification methods. The use of two-dimensional plots and three-dimensional plots obtained from the correspondence analysis of these matrices is explored, and the advantages of other graphical means, including the dendrogram, to visualise the association between these categories are briefly considered.
Keywords: Sulphates